Oncology Pharmacist's Role and Impact on the Multidisciplinary Patient-Centre Practice of Oncology Clinic in Public Hospitals - Chu Man Hin; Chong Chung Hong (ACHSM, 2019)
Oncology pharmacy service was developed and integrated into the multidisciplinary team of oncology clinic in 2013 at the United Christian Hospital aiming to enhance the holistic patient-centre practice of the clinic through the optimization of the safety and efficacy of anti-cancer treatment. This review aims to describe the role and impact of oncology pharmacists (OPs) in clinical setting to optimize anti-cancer treatment for cancer patients in a multidisciplinary care approach. From selection, prescribing, procurement to monitoring and patient education, OPs significantly contribute to the safety and effective use of anti-neoplastics in any circumstances. OPs provide professional advices to oncologists in choosing the appropriate anti-cancer agents for specific cancer and designing personalized anti-cancer treatment according to patients' fitness and appropriateness for chemotherapy. Parenteral and oral chemotherapeutic agents carry heightened risk of causing significant patient harm when they are used in errors. Thus, OPs also develop standardized chemotherapy orders and ensure the final dose is appropriate in terms of both hematological and non-hematological responses and tolerability. Moreover, OPs play an important role in procuring anti-cancer drugs and sourcing alternative drug choices that will deliver similar clinical outcomes. In addition, OPs also assure the clinical integrity of anti-cancer drugs for full anti-neoplastic activity and safe administration of these drugs by nursing staff to minimize potential occupational risk. Most importantly, OPs play a vital role in providing direct patient care functions such as drug therapy monitoring and management (e.g. ensure that patients receive sufficient pre-medications for administration of anti-cancer drugs), and medication counseling for patients and their carers to better understand their anti-cancer treatment. The positive impact of integrating OPs into the multidisciplinary patient-center practice of oncology clinic includes (1) reduction in potentially life-threatening medication incidents and cancer drug administration errors in public hospitals; (2) collaboration with oncologists to select the most suitable cancer drug regimens for patients; (3) prevention of potential occupational risk to the healthcare professionals who handle cancer drugs; and (4) provision of optimal therapy treatment, monitoring and counseling to patients to reduce side effects and hospital readmission. The professional drug knowledge of OPs adds value to the multidisciplinary team in oncology clinics and the growth of OPs into effective direct patient care in oncology clinics should be encouraged to optimize medication-related outcomes.